SIZE COMPOSITION, DISTRIBUTION, LENGTH-WEIGHT RELATIONSHIP AND NATURAL FOOD OF THE BLUE CRAB, Portunus pelagicus (L.) IN SELECTED COASTAL WATERS IN LEYTE AND VICINITY, PHILIPPINES - Batoy, Corazon B. (Annals of Tropical Research, 1988)
Female blue crabs were relatively smaller than males. More smaller crabs (carapace lengths <50 mm) were observed in January, April and July in consonance with reported intense spawning periods. Most crabs (males and females) were generally between 60 to 70 mm long. Spatial distribution was size-related with the larger crabs (carapace lengths > 50 mm) usually caught at depths greater than 6 meters and juvenile ones (carapace lengths <30 mm) found in shallower portions or near the shore. This distribution apparently resulted from migration patterns which are probably responses to the necessities of breeding, molting and feeding and is affected by salinity and substratum. Females were slightly heavier than males. The natural dict composition of P. pelagicus in descending order of percentage occurrence in its guts includes Osteichthyes, Holothuroidea, Algae, Echinoidea, Anomura, Bivalvia, Porifera, Brachyura, Penaeidea, Polychaeta, Foraminifera, Sea grass, Gastropoda, Copepoda, Amphipoda and Bryozoa. Food items particularly animals with hard parts were ingested in large recognizable pieces; few small food items were ingested in their entirety; others were ingested such that their soft tissues were almost completely separated from hard parts. Plant food was also ingested in fragments.